IN-VITRO BIOACTIVITY OF MARINE SEAWEED, CLADOPHORA RUPESTRIS - SUTHINDHIRAN KRISH; ABHINAB DAS (International Journal of Pharma and Bio Sciences, 2014)
Marine algae are rich source of biologically active compounds. This study was done to check the antioxidant, antimicrobial and antidiabetic activity of Cladophora rupestris. In phytochemical analysis, lipid, protein, alkaloid, flavonoids are found to be present. In the antioxidant activity, methanol, ethyl acetate & ethanol extract showed inhibition of 78%, 72% & 63% in 5 mg/ml respectively. Well diffusion method was done to check the antimicrobial property against human and shrimp pathogenic bacteria. MIC test was done to check the inhibition of the pathogenic bacteria at minimum concentration of crude extracts. In α-amylase inhibitory assay, methanol, ethanol and ethyl acetate extract showed highest inhibition of 72%, 65% & 70% at 1000 μg/ml. In α-glucosidase inhibitory assay, methanol and ethyl acetate showed highest inhibition of 67%, 61% and 64% at 1000 μg/ml.